2019
DOI: 10.1166/jnn.2019.16666
|View full text |Cite
|
Sign up to set email alerts
|

Cu-Doped SnO2 Nanoparticles: Synthesis and Properties

Abstract: In this work, a simple, co-precipitation technique was used to prepare un-doped, pure tin oxide (SnO2). As synthesized SnO2 nanoparticles were doped with Cu2+ ions. Detailed characterization was carried out to observe the crystalline phase, morphological features and chemical constituents with opto-electrical and magnetic properties of the synthesized nanoparticles (NPs). X-ray diffraction analysis showed the existence of crystalline, tetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 0 publications
4
14
0
Order By: Relevance
“…The results from both methods indicated that as the doping concentration increased from 1% to 4%, the crystal size decreased. A similar trend of change in crystal size was reported by different literatures [37,38] for Cu-doped SnO 2 nanoparticles. This decrease in crystal size of SnO 2 as the Cu-doping level increases suggesting that the growth was suppressed due to doping of Cu 2+ ion into Sn site.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The results from both methods indicated that as the doping concentration increased from 1% to 4%, the crystal size decreased. A similar trend of change in crystal size was reported by different literatures [37,38] for Cu-doped SnO 2 nanoparticles. This decrease in crystal size of SnO 2 as the Cu-doping level increases suggesting that the growth was suppressed due to doping of Cu 2+ ion into Sn site.…”
Section: Resultssupporting
confidence: 89%
“…This decrease in crystal size of SnO 2 as the Cu-doping level increases suggesting that the growth was suppressed due to doping of Cu 2+ ion into Sn site. This can be attributed to the incorporation of Cu 2+ ion in the host lattice to create more nucleation sites which would increase the lattice strain by slowing down the growth of the crystals [37,39]. The density of dislocation (δ = 1/D 2 ) [35,40], where D is the crystallite size from Scherrer's formula, caused by the microstructural strain and other defects seen to increase as Cu-doping increased in the host lattice (Figure 3(b)).…”
Section: Resultsmentioning
confidence: 99%
“…For mineral or mineral salt homeopathic medicine sources, the source materials may serve as dopants that tune the properties of whatever nano-structures form. [12][13][14][15] In the present model, electromagnetic and/or optical (photon-based) information, including quantum mechanical, arises from the manufacturing procedures. 16 There is nano-science evidence that the body would recognize the personal salience of the homeopathic potency signal to its current disease state because of the personalized protein corona shell from the recipient individual's own biomolecules that would immediately adsorb to form a coating around the surfaces of the medicine-related nano-structures on contact with the individual's biological fluids.…”
Section: Introductionmentioning
confidence: 99%
“…We know copper oxide as a p-type semiconductor in two stable forms, cupric oxide (CuO) and cuprous oxide (Cu 2 O) and this latter enables higher conversion efficiency when used as an absorber material for solar cell applications [4,5]. Moreover, the possibility of synthesizing nanoparticles enables excellent properties and opens the way to a new class of innovative and more efficient devices [6]. The ability to control the conductivity type can be important for the synthesizing of Cu 2 O thin films paired with other p-type materials.…”
Section: Introductionmentioning
confidence: 99%